The effect of sowing dates and sowing rates of wintering peas when cultivated in the southern part of the Rostov region on the economic efficiency of grain production - S. A. Vasilchenko; G. V. Metlina (Зерновое хозяйство России, 2024)
The current paper has presented the results of field trials carried out at the FSBSI “ARC “Donskoy” in 2019–2021 to study individual elements of cultivation technology (sowing dates, sowing rate) of wintering peas.   The purpose of the study was to estimate the effect of sowing dates and sowing rates of wintering peas when cultivated in the southern part of the Rostov region on the economic efficiency of grain production.   When cultivating wintering peas in the southern part of the Rostov region, the largest shares of costs have been spent on pesticides and seeds and were, respectively, 43.7–38.4 % and 25.4–35.9 % for the variety ‘Zimus’; 44.4–39.2 % and 23.9–34.3 % for the variety ‘Fokus’; 45.9–41.0 % and 20.7–30.6 % for the variety ‘Faeton’. The maximum gross income of 42,370 rubles/ha from the sale of wintering pea grain was obtained from the variety ‘Fokus’ in the third sowing period in the variant with a seeding rate of 1.4 million pcs. of germ. seeds/ha. The maximum conditional net income of 16,798 rubles/ha wasnoted for this variety in the second sowing period with a seeding rate of 1.2 million pcs. of germ. seeds/ha. The minimum production cost of 11,052 rubles/t was obtained from the variety ‘Fokus’ in the third sowing period with a seeding rate of 1.0 million pcs. of germ. seeds/ha, the maximum level of profitability of 72 % was noted in the same option. For the variety ‘Faeton’, grain was sold on 37,430 rubles/ha in the first sowing period at a seeding rate of 1.2 million pcs. of germ. seeds/ha. Also in this option, the highest conditional net income was 14347 rubles / ha with the lowest cost of production of 11717 rubles/ton and the maximum level of profitability of 62 %. For the variety ‘Zimus’, the maximum gross income from grain sales was 41420 rubles/ha with a seeding rate of 1.4 million pcs. of germ. seeds/ha in the second sowing period. In the same option, the highest conditional net income was 14423 rubles/ha, the lowest cost of production was 12384 rubles/t with the highest level of profitability of 53 %.